Complement factor C5 in Atlantic salmon (Salmo salar): Characterization of cDNA, protein and glycosylation. (November 2019) - Johansen, Wenche; Grove, Søren; Anonsen, Jan Haug; Moen, Anders; Agusti-Ridaura, Celia; Azar, Amir Sefidmouy; Strætkvern, Knut Olav
Abstract: Complement component 5 (C5) is an essential factor of the defensive complement system in all vertebrates. We report the characterization of C5 cDNA and protein from Atlantic salmon ( Salmo salar ), a teleost fish species of high importance in aquaculture. The C5 cDNA cloned from liver is 5079 nucleotides long, whose translation product has a molecular weight of 190 kDa, with the classical β-α orientation and motifs/sites for β-α cleavage ( 678 RPKR 681 ) and cleavage by C5 convertases (R 758 ). Mass spectrometric analysis show a single N-linked, biantennary, complex glycan at N 1125 . Moreover, the N-linked glycan displays an unusual modification in the form of acetylated sialic acid residues. Three anti-C5 antisera produced in mice using purified C5 worked in immunohistochemical analyses of formalin fixed liver tissue. The purification method, whereby inactive and activated (C5b) forms were isolated, opens for interesting studies on the complement function in fish, including possible connection to stress, disease and glycosylation. Highlights: Atlantic salmon C5 has β-α chain orientation and motifs for chain ( 678 RPKR 681 ) and convertase (R 758 ) cleavage. Purified salmon C5 protein has MW of 170 kDa while C5α is 95–100 kDa and C5β 60 kDa. First time reported, salmon C5 is glycosylated at N 1125 with multiple unusual glycoforms. Mouse antisera recognize both C5 and the C5α and C5β chains, and work in IHC. Purification method of glycosylated C5/C5b provides biomarker tool of stress response.